298 Falls and Syncope in Older People in the Emergency Department: Prevalence, Clinical Characteristics and Outcomes. (16th September 2019) - Bourke, Robbie; Rice, Ciara; McMahon, Geraldine; Cunningham, Conal; Anne Kenny, Rose; Briggs, Robert
Abstract: Background: Falls, syncope and presyncope comprise a large proportion of emergency department (ED) presentations among older people, however accurate data detailing this is limited. The aim of this study therefore was to ascertain the percentage of ED presentations in older people due to falls/syncope/presyncope, and examine admission rates, length of stay and likely underlying diagnosis. Methods: Over 1, 300 consecutive presentations of older people (aged ≥60 years) to the ED of a large urban university teaching hospital in March 2018 were examined (electronic and hard-copy notes) to ascertain the prevalence of falls/syncope/presyncope presentations. Data was collected for each presentation with fall/syncope/presyncope on demographics, and relevant clinical characteristics, including admission outcome and length of stay (LOS). Results: Falls/syncope/presyncope comprised 19% (250/1, 324) of presentations of older people to the ED, with a mean age of 75.3 +/-0.64 years. Almost 60% (158/250) presented during 'normal' working hours, i.e. Monday to Friday, 0800-1800. Almost half (121/250) had a Manchester Triage Score (MTS) of 3, indicating a need for urgent care, while one third (93/250) were categorized as requiring very urgent or immediate assessment (MTS 2 or 1 respectively). Over one third (97/250) presented with explained/accidental falls, while 26% (66/250) and 35% (87/250) presented with syncope and unexplained falls respectively. One in two (118/250) older people presenting with falls/syncope/presyncope were admitted to the acute hospital, and this rises to almost two thirds (82/135) of those aged ≥75 years. The median LOS was 15 (9.9 -22.0) days. Conclusion: Older people frequently present to the ED with falls/syncope/presyncope. The majority present during working hours and admission rates and LOS are relatively high. Falls/syncope/presyncope therefore represent an appropriate target for structured, multidisciplinary assessment at the 'front door' to provide early specialist assessment and management, and reduce complications associated with unnecessary admission to hospital.